Nurse’ Knowledge and Their Performance on Cardiopulmonary Resucitation (CPR) in Critical and Emergency Care Unit - Andriyani, Selvya Hesti; Setyorini, Fitri Ariani; Dewi, Enita; Pratiwi, Arum (Universitas Muhammadiyah Yogyakarta, 2019)
Background: Knowing the important relation between knowledge and skill is important because it reflexes the action that nurses do to save people life. Objective: This research aimed to determine the relationship between the nurse's knowledge level and their performance on cardiopulmonary resuscitation in critical and emergency care unit. Method: The study was quantitative descriptive with the cross-sectional design used sequential sampling with 30 nurses in critical and emergency care unit. The data were analyzed using the Fisher Exact Test. Data was taken from questioner and observational assessment using a standard operating procedure which was developed by a hospital. Results: The results of this study found that there were 63.3% respondents which all of them had poor knowledge also poor performance on doing cardiopulmonary resuscitation. Conclusion: There is a relation between nurse’s knowledge level and the nurse’s performance on undertaking cardiopulmonary resuscitation. The more knowledge they have the better performance they have on cardiopulmonary resuscitation. Routine training and evaluation may be useful to increase nurses’ knowledge and skills.